Surveillance of Aeromonas sobria and Aeromonas hydrophila from commercial food stuffs and environmental sources - Das, Arunava; Vinayasree, V; Santhosh, C R; Sree Hari, S (Journal of Experimental Sciences, 2013)
In tropical countries like India, commercial food items are often contaminated by various food-borne pathogens. Present research work reports the surveillance of A. sobria and A. hydrophila from commercial food stuffs and environmental sources across Tamil Nadu and Kerala, India. Samples were aseptically collected throughout the year and processed for isolation and identification of A. sobria and A. hydrophila. Isolates of Aeromonas were characterized for arrays of biochemical and phenotypic traits and finally assayed for antibiotic susceptibility test. A total of 71 suspected Aeromonas strains were isolated from 154 commercial food and environmental samples. Upon biochemical characterization of these isolates, 56(79%) were identified as A. sobria and remaining 15(21%) isolates were A. hydrophila. Upon detailed biochemical and phenotypical investigation, distinguishable results were obtained on esculin hydrolysis, acid production from L- arabinose, amylolytic, lipolytic and nuclease activities. All the isolates were 100% resistance to ampicillin, carbenicillin, cephalothin and clindamycin; 100% sensitive to colistin and moderate to cefuroxime, chloramphenicol, nalidixic acid, neomycin and nitrofurantoin. The present research suggested that colistin could be useful for motile Aeromonas infection but there has also been prevalence of multi drug resistant strains of Aeromonads in the Sothern states of India. The results aided our efforts to prove the strong occurrences of A. sobria and A. hydrophila as food borne pathogens in human consumable foods than in the environmental samples.